Aplikasi Trichoderma koningii dan Pseudomonas berfluoresensi untuk Pengendalian Penyakit Cabai di Minahasa, Sulawesi Utara - Johanna Maartje Paath; Max Ratulangi (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Major diseases on chili in Minahasa are bacterial wilt, anthracnose, and mosaic caused by virus infection. The objectives of this research were to evaluate the effectiveness of two microbes, Trichoderma koningii and fluorescent Pseudomonas, as biocontrol agents for major diseases of chili. Field experiment was conducted in Toure Village, Tompaso Baru, District of Minahasa. The treatments used were without biocontrol agents, T. koningii, fluorescent Pseudomanas, combination of T. koningii and fluorescent Pseudomanas. The results indicated that application of T. koningii, fluorescent Pseudomonas, and combination of the two biocontrol agents were only successfully suppressed incidence of bacterial wilt, but not of anthracnose nor mosaic diseases. Combination of the two biocontrol agents were able to improve yield of chili.